Clinical utility of mid-arm muscle circumference cut-offs for detecting protein-energy wasting in Malaysian hemodialysis patients - Hoong, Qian Qian; Lim, Jun Hao; Teong, Lee Fang; Adanan, Nurul Iman Hafizah; Khor, Ban Hock; Sahathevan, Sharmela; Khosla, Pramod; Karupaiah, Tilakavati; Mat Daud, Zulfitri Azuan (Elsevier B.V., 2025)
Objective: Protein energy wasting (PEW) is a severe form of malnutrition prevalent among hemodialysis (HD) patients. A key diagnostic criterion outlined by the International Society of Renal Nutrition and Metabolism (ISRNM) for PEW is a reduction in mid-arm muscle circumference (MAMC) below the 50th percentile (P50) of the reference population by more than 10%. However, the absence of population-specific MAMC cut-offs makes diagnosing PEW challenging. This study aimed to establish, validate and evaluate MAMC cut-offs for diagnosing PEW in Malaysian HD patients. Methods: A three-phase cross-sectional study was conducted with training, validation and testing phases using a five-fold cross-validation approach against Frisancho reference. A total of 953 Malaysian HD patients were included in the analysis. Secondary data from previous Malaysian HD studies were utilized for both the training and validation phases, accounting for about 85% of the dataset. The remaining 15% of the dataset, used for the testing phase, comprised newly collected data. Data collection involved face-to-face interviews, anthropometric measurements, biochemical results, clinical data, and dietary assessments. PEW was diagnosed using the ISRNM criteria. Descriptive analysis was used to establish Malaysians HD MAMC cut-offs at P50 for PEW diagnosis, as per ISRNM criteria. The area under the curve (AUC) of the receiver operating characteristics curve assessed and compared the validity of these new cut-offs against the Frisancho reference. Results: The P50 MAMC for Malaysian HD males was markedly lower than the Frisancho reference (24.29 cm vs 28.08 cm), whereas for females, it was slightly higher (23.14 cm vs 22.17 cm). The newly established Malaysian HD-specific MAMC cut-offs demonstrated excellent discrimination ability, outperforming Frisancho cut-offs for both validation (AUCMalaysian = 0.904 vs AUCFrisancho = 0.812) and evaluation (AUCMalaysia = 0.871 vs AUCFrisancho = 0.749). Conclusion: These MAMC cut-offs serve as the first Malaysian HD-specific references, enhancing PEW diagnosis for clinical practice and future research.